(untitled) (Bioagro, 2021)
The mango ‘Azucar’ is cultivated in the Department of Magdalena, Municipalities of Santa Marta and Ciénaga mainly, a place where it expresses its best agronomic behavior and the best fruit quality. The objective of this trial was to determine general standards of nutrients at the foliar level and to quantify the extraction of nutrients by the fruit during the development cycle of the plant, in addition to performing a nutritional diagnosis through the implementation of two diagnostic methods, the integrated diagnostic system and recommendation (DRIS) and the deviation from optimal percentage (DOP). Significant correlations were identified between productivity and the concentrations of P, K and Mg in foliar tissue, and nutrient levels were defined for highly productive trees. The highest extraction per ton of fruit was for potassium in the three evaluated stages with 2.43, 2.24 and 1.67 kg of the nutrient, followed by nitrogen with 1.87, 1.27 and 1.29 kg·t-1. Among microelements, the highest extraction was for iron, followed by boron, with 3.88 and 1.37 g·t-1, respectively. The total extraction by mango ‘Azucar’ per ton of harvested fruit was close to 4 kg of nutrients distributed as follows: 43 % K, 33.72 % N, 8.38 % Ca, 6.56 % P, 4.69 % Mg and 2.61 % S, with 1.04 % for the rest of nutrients. The order of nutritional requirement from the greatest deficiency determined by DRIS was Mn>Cu>Fe>N>P>S and by the DOP method Cu>N>S>Mg>Fe>P.